2020
DOI: 10.1088/1755-1315/443/1/012080
|View full text |Cite
|
Sign up to set email alerts
|

Autoclave-assisted weak acid pretreatment of oil palm empty fruits bunches for fermentable sugar production

Abstract: Pretreatment of oil palm empty fruit bunches (OPEFB) catalyzed by weak acids (oxalic, formic, and citric acid) in an autoclave under moderate condition is one of the appropriate pretreatment alternatives to recover reducing sugar both from cellulose and hemicellulose. This sugar can be fermented to be various bioprocess products. In this study, the effect of weak acid concentration (1–5% for oxalic acid; 5–20% for formic and citric acid), pretreatment temperature (115–125°C), time (60–90 min), and solid loadin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…The more furfural was formed, the lower xylose was obtained. The study reported by also had proven that the increase of acid concentration, time, and temperature significantly influenced the decrease of reducing sugars, including xylose, for other acids type such as oxalic, formic, and citric acid [39]. proposed twostage treatment to optimize the reducing sugar yield at the mild condition [40].…”
Section: A Hydrolysate Compositionmentioning
confidence: 99%
“…The more furfural was formed, the lower xylose was obtained. The study reported by also had proven that the increase of acid concentration, time, and temperature significantly influenced the decrease of reducing sugars, including xylose, for other acids type such as oxalic, formic, and citric acid [39]. proposed twostage treatment to optimize the reducing sugar yield at the mild condition [40].…”
Section: A Hydrolysate Compositionmentioning
confidence: 99%
“…The main challenge of enzymatic hydrolysis was the presence of lignin with a rigid structure that obstructed enzyme access in degrading cellulose and hemicellulose [9][10]. Thus, the lignin amount should be minimized from the solid fraction and destructed by the pretreatment process [11]. Assorted methods of pretreatment had been considerably reported.…”
Section: Introductionmentioning
confidence: 99%